2016
DOI: 10.1080/10773525.2015.1125585
|View full text |Cite
|
Sign up to set email alerts
|

Mercury and neuromotor function among children in a rural town in Chile

Abstract: Elemental Hg exposure in the household might have adverse long-term effects on children's pure motor skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…Children are also at risk of exposure to toxic levels of Hg due to participation in amalgam burning or by being in the proximity of the amalgam burning sites. Some of these children have been shown to exhibit long-term neurological deficits (Ohlander et al 2016), suggesting that they have been exposed to toxic levels of Hg.…”
Section: Introductionmentioning
confidence: 99%
“…Children are also at risk of exposure to toxic levels of Hg due to participation in amalgam burning or by being in the proximity of the amalgam burning sites. Some of these children have been shown to exhibit long-term neurological deficits (Ohlander et al 2016), suggesting that they have been exposed to toxic levels of Hg.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of using these biomarkers is due to the fact that they are considered highly accurate for measuring exposure to heavy metals (Park and Zheng, 2012). Hair and blood are often used as the best markers to measure neurotoxic and/or neurofunctional impact in populations exposed to these metals (Marques et al, 2013;Ohlander et al, 2016).…”
Section: Sampling For Exposure Biomarkersmentioning
confidence: 99%
“…In the 1960s, Pb was emerging as a major public health problem that might cause permanent brain damage [ 15 ]. Furthermore, several studies have reported that heavy metals can transfer across the placenta to the fetus, and may cross the blood–brain barrier (BBB) to directly affect the central nervous system, which may subsequently contribute to adverse neurodevelopmental outcomes involving cognition and sensorimotor functions [ 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%